Mechanisms of disease transformation in myeloproliferative neoplasms - O'Sullivan, J (2022)
Myeloproliferative neoplasms are heterogeneous clonal haematological malignancies where disease initiation occurs by acquisition of a somatic mutation in a haematopoietic stem cell. This mutation most often occurs in a janus kinase-signal transducer and activator of transcription signalling gene which drives constitutive janus kinase-signal transducer and activator of transcription signalling, with ensuing clonal expansion of downstream progenitor cells. Importantly, intra-tumoural cellular and molecular heterogeneity underscores the phenotypic heterogeneity of myeloproliferative neoplasms. Various factors drive disease progression but additional somatic mutations contribute significantly. Current myeloproliferative neoplasm therapies show limited effects on modifying disease biology and treatment resistance is common, associated with disease progression. Understanding whether distinct mutational profiles are associated with treatment resistance and examining the molecular signatures of mutant disease- driving haematopoietic stem and progenitor cells may reveal novel therapeutic targets and most importantly, lead to development of new treatments for these patients. Single-cell genomics approaches are ideally placed to achieve this through multi-omic technologies that can isolate mutant and non-mutant disease-driving stem and progenitor cells.